Effect of a respiratory disease challenge on nitrogen retention, IGF-I, organ weight and carcass characteristics in growing pigs - Loughmiller, J.A.; Fenwick, B.W.; Hogge, S.; Walker, J.; Stott, R.D.; Moser, A.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-seven growing pigs (initially 65 ± 2 lb) were used in a metabolism study to determine the effects of a single respiratory disease challenge on nitrogen retention, plasma insulin-like growth factor-I (IGF-I), organ weight, and carcass characteristics. Thirty pigs were challenged with Actinobacillus pleuropneumonia, and 7 pigs were assigned to an ad libitum fed nonchallenged control group. Ten additional nonchallenged pigs were pair-fed the feed intake of a A. pleuropneumonia-challenged counterpart. There were five 4 d collection periods (d 4 to 7, d 8 to 11, d 12 to 15, d 16 to 19, and d 22 to 25), and the A. pleuropneumonia challenge occurred on d 8. Plasma IGF-I concentrations decreased on d 9 in the disease challenged pigs compared to those in both nonchallenge treatments. Nitrogen retention was decreased during the immune challenge period and only partially recovered by the end of the experiment on d 25. Final organ weights and carcass characteristics were similar among treatments. These results suggest that a single acute respiratory disease challenge is accompanied by partial long-term compromises in protein metabolism and lean growth rate.
Keywords: Swine; Pigs; Nitrogen retention; Respiratory disease challenge